"Green Knowledge Community, Beats for Gaza": Transnational linkages and institutional obstacles to the diffusion of arts and permaculture-based resilience knowledge among youth in Gaza. (1st January 2020) - Esteves, Ana Margarida; Abusalama, Majed
Abstract : This article offers insights on how the institutional and material limitations, posed by the Israeli/Egyptian blockage on Gaza, promote learning processes that impact the strategic choices of an activist collective. It uses ethnographic data to explore micro processes of reasoning and decision-making in "Green Knowledge Community, Beats for Gaza", a network of Palestinian and international group of young activists aiming to promote grassroots-level resilience to Israeli occupation in this Palestinian territory. It analyses the shift from an initial focus on building an arts therapy school, which turned out to be unfeasible due to limitations both of the ground and among potential international donors, to a focus on permaculture, regarded as a strategy that could circumvent those limitations by mobilizing endogenous resources. The collective became progressively aware of the need to direct transnational knowledge diffusion to the support of the struggle for food sovereignty and grassroots economic self-determination through the localizing of agricultural production. This was due to the circumstances of the Israeli military occupation, Israeli/Egyptian blockage and the inclusion of a significant amount of arable land in the Gaza/Israel buffer, as well as to strategic choices of international donors, as well as the Hamas government.